Uniting Tradition and Modernity: Scientific Paradigms of Pesantren-Based Universities - Sri Haryanto; Sukawi Sukawi; Mohammad Muslih (Nazhruna: Jurnal Pendidikan Islam, 2024)
This study investigates the process of internalizing pesantren values in the implementation of Islamic higher education at Universitas Sains Al-Qur'an (UNSIQ) Wonosobo. Data were collected through in-depth interviews, participant observation, and document analysis. The findings reveal that UNSIQ's scientific paradigm is rooted in the values of Ahlus Sunnah wal Jamaah and Pesantren principles, such as the Panca Jiwa Pesantren. This paradigm emphasizes the integration of knowledge and religion, rejects the dichotomy between the worldly and the hereafter, and directs knowledge toward achieving syar'i (Sharia-compliant) goals. The internalization of Pesantren values at UNSIQ includes principles such as al-Amanah (trustworthiness), al-Tawadlu' (humility), al-Istiqamah (steadfastness), al-Uswah al-Hasanah (good role model), al-Tawashshuth (moderation), at-Tasamuh (tolerance), at-Tawazun (balance), simplicity, al-Barakah (blessing), and Tawasul Ilmi (knowledge-seeking). Efforts to internalize these values are carried out through both academic and non-academic activities. As a result, UNSIQ aims to produce graduates who are not only intellectually capable but also possess spiritual resilience and noble character. This study contributes to the development of an Islamic higher education model that integrates pesantren values and aligns with societal needs.